Induction of interferon and cell death in response to cytosolic DNA in chicken macrophages. (June 2016) - Vitak, Nazarii; Hume, David A.; Chappell, Keith J.; Sester, David P.; Stacey, Katryn J.
Abstract: Responses to cytosolic DNA can protect against both infectious organisms and the mutagenic effect of DNA integration. Recognition of invading DNA is likely to be fundamental to eukaryotic cellular life, but has been described only in mammals. Introduction of DNA into chicken macrophages induced type I interferon mRNA via a pathway conserved with mammals, requiring the receptor cGAS and the signalling protein STING. A second pathway of cytosolic DNA recognition in mammalian macrophages, initiated by absent in melanoma 2 (AIM2), results in rapid inflammasome-mediated pyroptotic cell death. AIM2 is restricted to mammals. Nevertheless, chicken macrophages underwent lytic cell death within 15 min of DNA transfection. The mouse AIM2-mediated response requires double stranded DNA, but chicken cell death was maintained with denatured DNA. This appears to be a novel form of rapid necrotic cell death, which we propose is an ancient response rendered redundant in mammalian macrophages by the appearance of the AIM2 inflammasome. The retention of these cytosolic DNA responses through evolution, with both conserved and non-conserved mechanisms, suggests a fundamental importance in cellular defence. Highlights: Cytosolic DNA induces cell death and interferon mRNA in chicken macrophages. Induction of interferon-beta mRNA depends on cGAS and STING. Cell death is rapid and lytic, not apoptotic. Chickens lack AIM2, the mammalian initiator of DNA-dependent death. Several mechanisms of DNA-dependent cell death have evolved independently.